Evaluasi Pemberian Makanan Tambahan pada Ibu Hamil dengan Kekurangan Energi Kronis (KEK) dari Program Corporate Social Responsibility (CSR) di Wilayah Kerja Puskesmas Tegal Angus Kabupaten Tangerang Tahun 2022 - Pujiastuti, Sri; Sudiman, Herman; Ulfa, Laila (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2023)
The condition of pregnant women who are at risk of CED can cause a decrease in the ability of the muscles that support the birth process. This can cause prolonged labor as well as bleeding, which is dangerous for the mother. Based on this, PT. Agung Sedayu Group pays special attention to the condition of chronic energy deficiency in pregnant women by creating a supplementary food program in the form of a unique and complete menu in the hope of helping to reduce the prevalence of chronic energy deficiency in pregnant women. The aim of this research is to find out how to evaluate the provision of additional food to pregnant women with chronic energy deficiency (KEK) from the Corporate Social Responsibility (CSR) program in the Tegal Angus Community Health Center work area in 2022. This type of research applies the Mixed Methods method with a Sequential Explanatory design The design starting from the first step of the research was carried out using quantitative methods and the second step was carried out using qualitative methods. Secondary data collection techniques were taken from Community Health Center data, while primary data were collected using in-depth interviews. Data analysis was carried out using the Wilxocon test. The research results showed that there were differences in the nutritional status of KEK pregnant women seen from LiLA with a significance value of 0.000 (p